(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
The HABA technique is a technique used specifically to address the adjustment for accrual basis accounting introduced by Sulaiman and Adam in 2019. But this technique has never been implemented for virtual teaching and learning purposes before. Then, the suitability of the technique to be used during the pandemic Covid-19 academic calendar is still in question. Therefore, this study was conducted to determine the relationship between the implementation of the HABA technique via online classes towards students' performance and Student Learning Time (SLT) on an accrual basis adjustment. This study adopts bivariate regression to assess the relationship of the variables and is supported with descriptive statistics which are mean, median, and standard deviation. The sample of the study was students from the first semester of the diploma in accountancy of Polytechnic Mukah for two consecutive academic sessions which are sessions 2020 and 2021. This study finds that the HABA technique via online classes can positively influence students' performance on the accrual adjustment. Besides, this technique is also able to inversely influence the SLT of the students to study on the accrual basis adjustment. Based on this study, students that have been taught the technique have portrayed better results as compared to other students. In fact, they are also able to shorten their study time to study this respective topic. This led to a positive impact on students’ academic achievement for this course. In conclusion, this technique is suitable to be adapted to both physical and virtual teaching and learning approaches.